Health information anxiety in social media users during public health emergencies: A qualitative comparative analysis using attribution theory - Xiao Wenchang; Yang Xuanhui; Zeng Qun; Cheng Xiao (PLoS ONE, 2026)
This article investigates the mechanisms influencing health information anxiety among social media users during sudden public health emergencies, aiming to provide insights for managing social media users’ negative emotions in such contexts. By employing literature analysis and case studies and integrating Three-Dimensional Attribution Theory, the factors contributing to health information anxiety are classified into individual, informational, and situational dimensions. Questionnaire data were gathered via scenario simulation, and a Qualitative Comparative Analysis (QCA) method was used to validate causal configurations leading to health information anxiety among social media users. The findings indicate that, within the context of sudden public health emergencies, the emergence of health information anxiety is the result of the interplay among individual, situational, and informational dimensions. Specifically, six key factors, including event severity, involvement, textual sentiment, collective emotions, information overload, and information asymmetry, are identified as playing a critical role in the development of severe health information anxiety. Notably, the situational dimension is found to exert a crucial and decisive influence on the generation of health information anxiety among social media users.